Equilíbrio de fases e propriedades mecânicas da liga de elemento multiprincipal Cr40Co40Ni20 - Bertoli, Gustavo (2021)
In the pursuit for materials with improved performance, multi-principal element alloys (MPEAs) attract the interest of the scientific community, due to their large composition space. Some Cr-Co-Ni alloys stand out with excellent toughness values, among the toughest materials ever made. The notorious mechanical behavior of these alloys is mainly ascribed to the occurrence of twinning-induced plasticity (TWIP) and/or transformation-induced plasticity (TRIP). The present work studied the phase equilibria and mechanical properties of the Cr40Co40Ni20 MPEA, such composition was selected because it is located in a transition region between TWIP alloys and TRIP alloys of the Cr-Co-Ni system. In this work, thermodynamic calculations using the CALPHAD method predicted the formation of a sigma phase, which is often undesirable. Experimentally, the sigma phase could be completely suppressed by kinetic factors, so the alloy presented a matrix with face-centered cubic (FCC) structure, annealing twins, and a second phase: possibly 9R phase and/or cooling-induced hexagonal close-packed (HCP) martensitic phase. These structures with fine morphology provided interface hardening, which contributed to the high intrinsic yield strength (σ0) of 299 MPa, obtained by a Hall-Petch study in tensile tests. The alloy also showed an efficient grain refining strengthening of 667 MPa/µm-0.5 and optimal combinations of mechanical strength and ductility, in addition to high toughness. The explanation for this performance is the high work hardening capacity, mainly ascribed to TRIP and possibly TWIP. In dry-sliding wear tests against alumina pins, the alloy exhibited good wear resistance and a low coefficient of friction (CoF) of 0.12. The present results further evidence the high potential of Cr-Co-Ni alloys, particularly the studied composition, in applications which this set of properties is necessary.